Conceptual framework on - establishing healthy life style centre in Chhattisgarh state, India - Jain, Kamlesh Kumar; Tiwari, Anjana; Bhawnani, Dhiraj (International Journal of Research in Medical Sciences, 2017)
Lifestyle diseases characterized by those diseases whose occurrence is primarily based on the daily habits of people and are a result of an inappropriate relationship of people with their environment. The main factors contributing to lifestyle diseases include bad food habits, physical inactivity, wrong body posture, and disturbed biological clock. Lifestyle diseases are the most common causes of disability, morbidity and premature mortality. They account for 52% of deaths, 43% Disability Adjusted Life Years (DALYs) and 62% of total disease burden in India. Life style disease can be prevented through focused and comprehensive public health intervention by establishment of Healthy Life Style Centre (HLSC). HLSC will be a comprehensive approach which will provide health services for Non-Communicable diseases under the one roof. The HLSC will offer consultation, learning, counselling and testing facilities regarding Diabetes and other Non-Communicable diseases (NCD). Life style diseases can be prevented through public health intervention by special task force and policy document related to life style disorders.